Indonesia Economic Quarterly, December 2011 : Enhancing Preparedness, Ensuring Resilience - World Bank (World Bank, Jakarta, 2017)
International financial markets remain turbulent, dominated by the political and economic challenges of the Euro zone debt crisis and signs of weakening global growth. However, to date, although portfolio outflows have been seen, Indonesia's domestic economy continues to perform strongly. The economy remains relatively well-positioned to weather future external shocks and steps have been taken to improve crisis preparedness, for example, by increasing the flexibility of any fiscal response. The Euro zone continues to grapple with the policy responses to stem the crisis. The political and policy responses to the Euro zone debt crisis have been evolving on an almost daily basis, influencing global financial markets, risk appetite and capital flows to emerging economies such as Indonesia. Increased funding stress for European financial institutions was followed by a coordinated announcement of liquidity swap arrangements by central banks including the Federal Reserve and European Central Bank. In addition to putting in place policies to address the near-term impacts of any future shocks, with a protracted weakness in external demand likely, it is an opportune time to move forward with investments and reforms which can enhance domestic productivity and growth and attract more stable and longer-term capital flows. Indeed, the 2012 budget again significantly boosts capital expenditure, although ongoing budget execution challenges could hinder the effectiveness of the increased allocation on infrastructure improved infrastructure and investment climate can help to promote further the positive recent performance of Indonesia's manufacturing sector, after its weakness in the decade following the Asian crisis. The scope for productivity growth within manufacturing and other sectors through technology adoption and adaption can also be enhanced by further improvements in the quality of education of the labor force and the institutional environment for research and development.